PERAN BRAND AMBASSADOR, BRAND IMAGE, DAN HARGA TERHADAP MINAT BELI KONSUMEN (STUDI KASUS CO-BRANDING SAMSUNG X BTS) - Agnes Arum Kusuma Wardani; Budi Istiyanto (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study aims to determine whether Brand Ambassador, Brand Image and Price affect the purchase intention of Samsung products. The method used by the author is a quantitative method. The sample used in this study is a purposive sampling method with an unlimited population. Samsung and ARMY users (BTS fans) who are 15-50 years old and domiciled in Solo Raya are the criteria in this study. The data analysis technique used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, T test, R test and R2 test. Based on the data processing, it was found that the Brand Ambassador variable had a positive and insignificant effect on buying interest. And the Brand Image and Price variables have a positive and significant influence on buying interest.Suggestions from the results of this research, Samsung should consider more about the Brand Ambassador that you want to partner with to increase sales and be consistent in considering Samsung's brand image and price according to the quality and features available. Keyword : Brand Ambassador, Brand Image, and Price